Reservists Called to Active Duty and the Effect on Human Resource Management - Nichole Schroeder; Julie Gatlin; Allen F. Wysocki; Karl W. Kepner; Derek Farnsworth; Jennifer Clark (EDIS)
This document discusses the impact of reservists being called to active duty on human resource management. It highlights the challenges faced by managers when employees are absent for extended periods due to military service. The article outlines the federal guidelines provided by the Uniformed Services Employment and Reemployment Rights Act (USERRA), which protects the employment rights of reservists. It also offers management recommendations for ensuring a smooth transition during such absences, including understanding USERRA regulations, planning for temporary replacements, and supporting reservist employees.